Fibroscan® probe selection for lean adults. Issue 7 (26th May 2021) - Stadlbauer, Vanessa; Negrean, Iohanes; Posch, Andreas; Streit, Andrea; Feldbacher, Nicole; Stauber, Rudolf E; Horvath, Angela
Abstract: Background and Aim: Fibroscan® is used to assess fibrosis and steatosis of the liver noninvasively. The company suggests to use the S+‐probe in people <18 years with a thoracic circumference (TC) between 45 and 75 cm and the M+‐probe in children with a TC >75 cm and adults with a skin–liver capsule distance <2.5 cm. For lean adults with a TC ≤75 cm, no comparative studies have been performed. Furthermore, it is unclear whether lean adults need to be fasted before assessment. Methods: We compared liver stiffness (LS) using Fibroscan® S+‐ and M+‐probes and controlled attenuation parameter (CAP; only available for M+‐probe) in healthy volunteers with a TC ≤75 cm compared with those with a TC >75 cm in fasting state and after intake of a standardized light meal (300 kcal). Results: We examined 50 volunteers (26 female, 24 ± 3 years). Twenty‐two participants were in the TC ≤75 cm group and 28 in TC >75 cm group. LS values with the S+‐probe were 15% higher than with the M+‐probe in both groups (median difference 0.6 kPa, P < 0.001). Both probes showed good agreement with minimal bias (Spearman correlation r = 0.754, P < 0.001; Interclass Correlation Coefficient 0.843, P < 0.001; Bland–Altman bias 0.6 ± 0.9 kPa, linear regression r 2 = 0.557, P < 0.001). Intake of a light meal had no relevant influence on LS (S+‐ and M+‐probes) or CAP measurements (M+‐probe) in both groups. Conclusion: Lean adults with a TC below 75 cm can be assessed with either the S+‐probe or the M+‐probe and may take a light meal before assessment. Abstract : Graphical extract was created using BioRender.com (TC, thoracic circumference; SCD, skin‐capsule distance). Lean adults with a thoracic circumference of <75 cm can be assessed with the S+‐ and the M+ probes of the Fibroscan (R). A light meal does not affect the measurements.